Characterization of humic substances isolated from a tropical zone and their role in membrane fouling. Issue 3 (June 2022) - Hansima, M.A.C.K.; Jayaweera, A.T.; Ketharani, J.; Ritigala, Tharindu; Zheng, Libing; Samarajeewa, D.R.; Nanayakkara, K.G.N.; Herath, Ajith C.; Makehelwala, Madhubhashini; Jinadasa, K.B.S.N.; Weragoda, S.K.; Wei, Yuansong; et al.
Abstract: Humic substances (HS) are heterogeneous organic polymers that show monotonous properties. HS are present at different proportions in the terrestrial environment, and they implicate the performance of water desalination plants. Recently electrodialysis self-reversal (EDR) technology has been used to treat excess salinity, hardness and fluoride in HS rich groundwater in Sri Lanka ( 3 mg L −1, dissolved C). Due to the high organic content of HS in groundwater, the EDR ion exchange membranes are prone to fouling. To unravel the fouling mechanisms, humic acid (HA) and fulvic acid (FA) fractions were isolated and fractionated from the groundwater and characterized spectroscopically. All membrane fouling experiments were conducted for HA and FA contaminated water using a lab-scale EDR setup operated under batch mode. Sequential desorption experiments were carried out using distilled water, 2% (w/w) NaCl, and 0.3% (w/w) sodium dodecyl sulfate to probe variations among two fouling mechanisms. Similarities were found in aromatic and aliphatic carbon contents, humification degree, and molecular weight of humic substances. Higher proportions of carboxylic and phenolic groups were found in FA compared to HA. Ester groups in HA facilitate P, S, and Si migration within organic moieties. The molecular environs in the vicinity of carboxyl functional groups led different fouling mechanisms. HA fouling was found irreversible compared to FA fouling. The subtle differences between fouling mechanisms will help implement appropriate pretreatments to ensure the durability of EDR membranes. Graphical Abstract: ga1 Highlights: Phosphates, sulfates, and silicates are ester bonded only with a humic fraction. Fouling anion exchange membranes by fulvic and humic fractions differ markedly. Membrane functionality deteriorates by humic fraction fouling.